Aetiology and Pathogenesis of Trigeminal Neuralgia: a Comprehensive Review - Gintautas Sabalys; Gintaras Juodzbalys; Hom-Lay Wang (Stilus Optimus, 2012)
Objectives: The aim of present paper was to discuss issues related to trigeminal neuralgia with strong emphasis on the aetiology and pathogenesis of this problem. Material and Methods: An electronic search of 5 databases (1965 - Oct 2012) and a hand search of peer-reviewed journals for relevant articles were performed. In addition, experience acquired from treating 3263 patients in the Department of Maxillofacial Surgery, Lithuanian University of Health Sciences, were also summarized. Results: Generally, aetiological factors can be classified into 3 most popular theories that were based on: 1) Related to other disease, 2) Direct injury to the trigeminal nerve, and 3) Propagates the polyetiologic origin of the disease. In addition, two pathogenesis mechanisms of trigeminal neuralgia were proposed. First: the peripheral pathogenetic mechanism that is often induced by progressive dystrophy around the peripheral branches of the trigeminal nerve. Second, central pathogenetic mechanism which often triggered by peripheral pathogen that causes long-lasting afferent impulsation and the formation of a stable pathologic paroxysmal type irritation focus on the central nerve system (CNS). Conclusions: Patients with susceptive trigeminal neuralgia should be examined carefully by specialists who have expertise in assessing and diagnosing of possible pathological processes and be able to eliminate the contributing factors so the trigeminal neuralgia can be properly managed.